2002
DOI: 10.1038/sj.ejhg.5200757
|View full text |Cite
|
Sign up to set email alerts
|

Lack of expression of XIST from a small ring X chromosome containing the XIST locus in a girl with short stature, facial dysmorphism and developmental delay

Abstract: A 46,X,r(X) karyotype was found in a three and a half year old girl with short stature, facial dysmorphism and developmental delay. The clinical findings were consistent with the phenotype described in a limited number of patients with small ring X chromosomes lacking the XIST locus, a critical player in the process of X chromosome inactivation. Surprisingly, in our patient, fluorescent in situ hybridisation demonstrated that the XIST locus was present on the ring X. However, expression studies showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
(24 reference statements)
2
30
0
Order By: Relevance
“…It has been shown that the severity in cases with small ring X chromosome is because of failure of small ring chromosome to be inactivated due to deletion of X-inactive specific transcript (XIST) at Xq13 [22,43]. In our cases, XIST was intact with the ring chromosome in both the cases negating the role of XIST inactivation in clinical phenotype of patients (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…It has been shown that the severity in cases with small ring X chromosome is because of failure of small ring chromosome to be inactivated due to deletion of X-inactive specific transcript (XIST) at Xq13 [22,43]. In our cases, XIST was intact with the ring chromosome in both the cases negating the role of XIST inactivation in clinical phenotype of patients (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Mutations of the XIST promoter can completely bias XCIRs. One dominant promoter mutation prevents the X chromosome carrying the mutant XIST from being inactivated, 24 whereas another causes the mutant X to always be inactivated. 21 Thus, XIST promoter mutations result in complete XCIR skewing (100:0).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation, X-chromosome inactivation (XCI), and genomic imprints are the most important epigenetic modifications. The appropriate initiation and maintenance of XCI is very important for embryogenesis and cell physiology [15]. Aberrant allele-specific imprinted gene expression can also cause genetic disorders, such as Prader Willi/ Angelman syndrome [16].…”
Section: Introductionmentioning
confidence: 99%